2018
DOI: 10.1007/s00330-017-5266-1
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between applied energy and ablation zone volume in patients with hepatocellular carcinoma and colorectal liver metastasis

Abstract: ObjectivesTo study the ratio of ablation zone volume to applied energy in computed tomography (CT)-guided radiofrequency ablation (RFA) and microwave ablation (MWA) in patients with hepatocellular carcinoma (HCC) in a cirrhotic liver and in patients with colorectal liver metastasis (CRLM).MethodsIn total, 90 liver tumors, 45 HCCs in a cirrhotic liver and 45 CRLMs were treated with RFA or with one of two MWA devices (MWA_A and MWA_B), resulting in 15 procedures for each tumor type, per device. Device settings w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 20 publications
2
35
1
Order By: Relevance
“…The amount of energy needed can also be planned with the planning software. However, recent studies have shown that the resulting ablation zones differ from the prediction based on the ex-vivo results that are provided by the ablation device manufacturers [26] and also depend on the tumor type [27].…”
Section: Ablationmentioning
confidence: 89%
“…The amount of energy needed can also be planned with the planning software. However, recent studies have shown that the resulting ablation zones differ from the prediction based on the ex-vivo results that are provided by the ablation device manufacturers [26] and also depend on the tumor type [27].…”
Section: Ablationmentioning
confidence: 89%
“…Current microwave and radiofrequency ablative therapies are most efficient for thermal ablation, where the goal is to raise the target tumor temperature to a lethal temperature, thereby inducing necrosis or apoptosis. 36 Instead, our platform provides fast, focused MH (43°C) to the target tissue only; a benefit of utilizing a laser heating source versus microwaves 37 39 or radiofrequency, 6 8 , 36 whose temperatures can exceed 100°C and 150°C, respectively, and can in some cases stimulate heat-induced tumor spreading. 40 By combining low-voltage NPS with a moderate amount of heat, we can mitigate theses deleterious effects providing high-power fast heating with an infrared laser.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, how can the manufacturers’ provided ablation algorithms ever predict the ablation zone in humans with diseased liver parenchyma, with various types of tumours and highly variable arterial and portal blood flow and in close contact with adjacent structures? The impact of tumour type was analysed in a clinical MWA study; we found that the ratio “ablation zone volume:applied energy” was higher in HCC tumours as compared to colorectal liver metastases . This suggests that also the tumour type is of relevance for the completeness of ablation: colorectal liver metastases require more energy than HCCs.…”
Section: Key Concepts and Developments For Successful Percutaneous Abmentioning
confidence: 94%